Stereotypic Behavior in Sows Is Related to Emotionality Changes in the Offspring - Tatemoto, Patricia; Bernardino, Thiago; Morrone, Beatrice; Queiroz, Mariana Ramos; Zanella, Adroaldo José (Frontiers in Veterinary Science, 2020)
Some effects of expressing stereotypic behaviour have not yet been elucidated. During gestation, the environment has the potential to interfere with offspring development and to have prenatal or longer-term consequences. We tested the hypothesis that the occurrence of stereotypic behaviour during gestation could affect the phenotype of the offspring. Twenty-eight pregnant sows were studied, by comparing two groups differing in the amount of stereotypy shown. We analysed emotionality in the offspring from sows showing high or low stereotypy frequency using open field and novel object tests. In the open field test, piglets from sows with a high rate of stereotypies walked more in central quadrants (p < 0.0001) and lateral quadrants (p = 0.04) than piglets from sows with low rate of stereotypies. In the novel object test the offspring from low stereotypy sows vocalized more (p = 0.008). We demonstrate for the first time that stereotypic behaviour by the mother during gestation changes the phenotype of the offspring, in particular their emotionality. This study was conducted according to the ethical principles of animal experimentation and under the approval of the Ethics Committee on Animal Use of the School of Veterinary Medicine and Animal Science (University of São Paulo, Brazil), protocol number 3606300114. Authors ensured that manuscript conforms to the ARRIVE Guidelines for Reporting Animal Research.